Pengaruh Penggantian Manajemen, Dewan Komisaris Independen, Kepemilikan Managerial, Kepemilikan Institusional, dan Kualitas Audit Terhadap Manajemen Laba - Andan Yunianto (Universitas Muhammadiyah Yogyakarta, Indonesia, 2013)
The purpose of this study is to find out empirical evidence that the management turnover positively affects the earnings management and composition of independent board of director, managerial ownership, institutional ownership, and the quality of auditing negatively affect the earnings management, which is measured by using an absolute discretionary accrual. Sample of the study is consisted of 76 firms with 166 firm years from panel data of all manufacturing companies listed in the Indonesian Stock Exchange from 2006 to 2009. The study uses an ordinary least square regression to test hypotheses proposed. Result of the study indicates that the management turnover, composition of independent board of director and institutional ownership did not affect the earnings management, while the quality of auditing positively affects the earnings management.